Label-free analysis of GPCR-stimulation: The critical impact of cell adhesion. (June 2016) - Lieb, S.; Michaelis, S.; Plank, N.; Bernhardt, G.; Buschauer, A.; Wegener, J.
Graphical abstract: Abstract: Label-free cell-based assays have been attracting growing attention in drug research. Optical approaches based on evanescent electric fields (e.g. EPIC, RWG/DMR, SPR) and electrochemical impedance analysis (ECIS, xCELLigence) are by far the most widespread techniques for such purposes. We compared three label-free approaches (ECIS, RWG/DMR and SPR) with respect to the activation of the human histamine H1 receptor (H1 R) expressed by U-373 MG glioblastoma and genetically engineered HEK 293T cells. HEK 293T cells were either expressing the hH1 R alone or in combination with the adhesion protein hMSR1. The β2 -adrenergic receptor (β2 -AR) expressed by bovine aortic endothelial cells (BAEC) served as a second cell model. Reduced cell adhesion to the surface of the sensing devices affected both, the optical and the impedance-based readout, but became much more obvious in case of RWG- or SPR-based assays. By contrast, the co-expression of hH1 R and hMSR1 in HEK 293T cells strongly enhanced the signal compared to hH1 R expression alone. As the sensitivity of the optical readouts is confined to a distance of 100–200 nm from the surface, depending on the wavelength of the incident light, this observation is in accordance with tighter adhesion of the co-transfectants, inducing a shorter distance between the cell membrane and the substrate. Combining ECIS and SPR, allowing for simultaneous registration of both signals for a single cell population, provided a direct correlation of both readouts, when H1 R or β2 -AR stimulation was investigated for the same cell populations. Cell adhesion was found to have a critical impact on the results of label-free cell monitoring, in particular when techniques based on evanescent electric fields are applied.